Tetraodon nigroviridis: A model of Vibrio parahaemolyticus infection. (September 2016) - Peng, Wan; Shi, Yu; Li, Gao-Fei; He, Liang-Ge; Liang, Yao-Si; Zhang, Yong; Zhou, Li-Bin; Lin, Hao-Ran; Lu, Dan-Qi
Abstract: Vibriosis is the most common bacterial diseases and brings great economic loss on aquaculture. Vibrio parahaemolyticus ( V. parahaemolyticus), a gram-negative bacterium, has been identified as one main pathogens of Vibriosis. The pathogenic mechanism of V. parahaemolyticus is not entirely clear now. In our study, a model of V. parahaemolyticus infection of green-spotted puffer fish ( Tetraodon nigroviridis ) was established . T. nigroviridis were injected intraperitoneally (i.p.) with 200 μL of V. parahaemolyticus (8 × 10 10  CFU/mL). V. parahaemolyticus infection caused 64% mortality and infected some organs of T. nigroviridis . Histopathology studies revealed V. parahaemolyticus infection induced tissue structural changes, including adipose hollow space in the liver. Immunohistochemistry showed V. parahaemolyticus were present in infected tissue such as liver, head kidney and spleen. In livers of T. nigroviridis infected by V. parahaemolyticus, the alkaline phosphatases (ALP) activity first gradually increased and then backed to normal level, a trend that was on the contrary to the expression profile of the miR-29b. Quantitative real-time PCR analysis showed that the expression level of TLR1, TLR2, TLR5, TLR9, TLR21, NOD1, NOD2 and IL-6 in response to V. parahaemolyticus infection decreased compared to that of non-infected fish. The establishment of the T. nigroviridis model of V. parahaemolyticus infection further confirmed V. parahaemolyticus spreads through the blood circulation system primary as an extracellular pathogen. Meanwhile, liver is an important target organ when infected by V. parahaemolyticus . miR-29b in liver was involved in the progress of liver steatosis during V. parahaemolyticus infection. Moreover, V. parahaemolyticus infection in vivo may have an effect of immunosuppression on host. Highlights: A model of Vibrio parahaemolyticus infection of Tetraodon nigroviridis was established. V. parahaemolyticus infection caused adipose hollow space in the liver of T. nigroviridis . miR-29b in liver was involved in the progress of liver steatosis during V. parahaemolyticus infection. Further confirmed that V. parahaemolyticus spreads through the blood circulation system as an extracellular pathogen. V. parahaemolyticus infection may have an effect of immunosuppression on host, showing a suppression of PRR expression.